Evaluation of Spatial Uncertainty and its Elements in Different Types of Spaces - Goncagül Altunışık; Hande Düzgün Bekdaş (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Uncertainty in the field of architecture is a concept that shapes the design process, free from negativity, and can be analyzed through various subcategories. Spatial uncertainty, one such category, refers to the undefined nature of factors influencing space and offers flexibility, presenting a forward-looking approach to innovation in architecture. It can be categorized into three aspects: functional, formal, and user-oriented, enabling these elements to be analyzed through space. Recognizing these distinctions helps clarify the concept’s complexity and assess its impact on the design process. For this purpose, spatial uncertainty elements will be examined through building examples selected from different types of spaces. To make the uncertainty levels measurable, the Shannon Entropy method will be used to evaluate the effects of spatial uncertainty on the design process, and a new perspective will be put forward in the literature.